MANAJEMEN MUTU DALAM PENGELOLAAN SDM PENDIDIKAN DAN MODEL PENINGKATAN MUTU PEMBELAJARAN ONLINE - Asnawi Asnawi (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT Quality management in educational human resource (HR) management is an important factor in improving educational quality, particularly in the digital era that requires adaptation to online learning. In the context of Islamic education, HR management focuses not only on administrative aspects but also on spiritual and moral development by positioning teachers as murabbi who play a role in shaping students’ character. This study aims to examine the role of quality management in Islamic educational HR management and to develop a quality-based online learning model to address the challenges of modern education. The study employs a library research method through the analysis of various literature sources, scientific articles, and relevant references related to quality management, Islamic educational HR management, and online learning. The research stages include literature collection, analysis of HR management concepts from an Islamic perspective, examination of quality management principles, design of a quality-based online learning model, and synthesis and interpretation of findings. The results indicate that the implementation of quality management principles in Islamic educational HR management can enhance teachers’ professionalism, competence, and performance quality. In addition, the quality-based online learning model, which includes planning, implementation, evaluation, and continuous improvement, is able to ensure the quality of the learning process through valid content, meaningful interaction, and objective assessment. By integrating the Total Quality Management (TQM) approach with Islamic educational values, online learning can serve as an adaptive, inclusive, and sustainable educational medium. The study concludes that quality management in HR management and online learning plays a strategic role in improving educational quality in a holistic manner. ABSTRAK Manajemen mutu dalam pengelolaan sumber daya manusia (SDM) pendidikan merupakan faktor penting dalam meningkatkan kualitas pendidikan, terutama pada era digital yang menuntut adaptasi terhadap pembelajaran daring. Dalam konteks pendidikan Islam, pengelolaan SDM tidak hanya berfokus pada aspek administratif, tetapi juga pada pembinaan spiritual dan moral dengan menempatkan guru sebagai murabbi yang berperan dalam pembentukan karakter peserta didik. Penelitian ini bertujuan mengkaji peran manajemen mutu dalam pengelolaan SDM pendidikan Islam serta mengembangkan model pembelajaran online berbasis mutu untuk menjawab tantangan pendidikan modern. Metode yang digunakan adalah studi kepustakaan (library research) melalui analisis berbagai literatur, artikel ilmiah, dan sumber relevan terkait manajemen mutu, pengelolaan SDM pendidikan Islam, serta pembelajaran daring. Tahapan penelitian meliputi pengumpulan literatur, analisis konsep manajemen SDM dalam perspektif Islam, kajian prinsip manajemen mutu, perancangan model pembelajaran online berbasis mutu, serta sintesis dan interpretasi temuan. Hasil penelitian menunjukkan bahwa penerapan prinsip manajemen mutu dalam pengelolaan SDM pendidikan Islam dapat meningkatkan profesionalisme, kompetensi, dan kualitas kinerja pendidik. Selain itu, model pembelajaran online berbasis mutu yang mencakup perencanaan, pelaksanaan, evaluasi, dan perbaikan berkelanjutan mampu menjamin kualitas proses pembelajaran melalui konten yang valid, interaksi bermakna, dan penilaian yang objektif. Dengan mengintegrasikan pendekatan Total Quality Management (TQM) dan nilai-nilai pendidikan Islam, pembelajaran daring dapat menjadi sarana yang adaptif, inklusif, dan berkelanjutan. Simpulan penelitian ini menegaskan bahwa manajemen mutu dalam pengelolaan SDM dan pembelajaran online berperan strategis dalam meningkatkan mutu pendidikan secara holistik.